2005
DOI: 10.1093/eurheartj/ehi442
|View full text |Cite
|
Sign up to set email alerts
|

The effect of micronutrient supplementation on quality-of-life and left ventricular function in elderly patients with chronic heart failure

Abstract: Long-term multiple micronutrient supplementation can improve LV volumes and LVEF and QoL scores in elderly patients with heart failure due to LV systolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
213
0
15

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(230 citation statements)
references
References 43 publications
2
213
0
15
Order By: Relevance
“…Witte et al presented data indicating that supplementation with micronutrients including selenium and coenzyme Q10 could improve cardiac left ventricular (LV) function according to evaluations made using cardiac magnetic resonance scans [59]. The authors also demonstrated a significant increase in quality of life as evaluated by the EuroQoL inventory (a European multidisciplinary inventory to evaluate the health status), but at the same time no change of the NYHA (New York Heart Association) functional class could be reported.…”
Section: Selenium and Coenzyme Q10 In Heart Diseasementioning
confidence: 99%
“…Witte et al presented data indicating that supplementation with micronutrients including selenium and coenzyme Q10 could improve cardiac left ventricular (LV) function according to evaluations made using cardiac magnetic resonance scans [59]. The authors also demonstrated a significant increase in quality of life as evaluated by the EuroQoL inventory (a European multidisciplinary inventory to evaluate the health status), but at the same time no change of the NYHA (New York Heart Association) functional class could be reported.…”
Section: Selenium and Coenzyme Q10 In Heart Diseasementioning
confidence: 99%
“…Although the regression of cardiac hypertrophy by dietary copper supplementation in humans is unknown, a recent study in a small population of chronic heart failure patients has shown that dietary supplementation with micronutrients for 9 months increased left ventricle ejection, decreased left ventricle volume, and improved the quality of life [2]. Among the formulated micronutrients was Cu (1.2 mg/day), which has been considered to play an important role in the improvement of cardiac function [3].…”
Section: Introductionmentioning
confidence: 99%
“…We were able to relate increasing levels of isoprostanes and reduced antioxidant concentrations to increasing NYHA functional class. In a previous study, multiple micronutrient supplementation, including the antioxidant vitamins C and E, improved left ventricular function and quality-of-life scores in a small group of elderly patients with CHF [31]. In contrast, antioxidant supplementation with vitamin E (a-tocopherol) alone did not help patients with CHF [32] and may even be harmful [33].…”
Section: Discussionmentioning
confidence: 89%